Emergence of Members of TRAF and DUB of Ubiquitin Proteasome System in the Regulation of Hypertrophic Cardiomyopathy - Gupta, Ishita; Varshney, Nishant K.; Khan, Sameena (Frontiers in Genetics, 2018)
The ubiquitin proteasome system (UPS) plays an imperative role in many critical cellular processes, frequently by mediating the selective degradation of misfolded and damaged proteins and also by playing a non-degradative role especially important as in many signaling pathways. Over the last three decades, accumulated evidence indicated that UPS proteins are primal modulators of cell cycle progression, DNA replication, and repair, transcription, immune responses, and apoptosis. Comparatively, latest studies have demonstrated a substantial complexity by the UPS regulation in the heart. In addition, various UPS proteins especially ubiquitin ligases and proteasome have been identified to play a significant role in the cardiac development and dynamic physiology of cardiac pathologies such as ischemia/reperfusion injury, hypertrophy, and heart failure. However, our understanding of the contribution of UPS dysfunction in the plausible development of cardiac pathophysiology and the complete list of UPS proteins regulating these afflictions is still in infancy. The recent emergence of the roles of TNF receptor-associated factor (TRAFs) and deubiquitinating enzymes (DUBs) superfamily in hypertrophic cardiomyopathy has enhanced our knowledge. In this review we have mainly compiled the TRAF superfamily of E3 ligases and few DUBs proteins with other well-documented E3 ligases such as MDM2, MuRF-1, Atrogin-I and TRIM 32 that are specific to myocardial hypertrophy. In this review, we also aim to highlight their expression profile following physiological and pathological stimulation leading to the onset of hypertrophic phenotype in the heart that can serve as biomarkers and the opportunity for the development of novel therapies.